Directed Self‐Organization Ensured Enhancement of Charge Carrier Mobilities in a Star‐Shaped Organic Semiconductor. Issue 49 (30th July 2020) - Birudula, Srikanth; Prabhu, Deepak D.; Ghosh, Tapan; B., Adara; Das, Suresh; Vijayaraghavan, Ratheesh K.
Abstract: Controlled self‐organization of organic semiconductor molecules into specifically desired architectures on substrates of interest is one of the most imperative challenges faced in the fabrication of high‐performance organic electronic devices. Herein, we report the self‐organization of a star‐shaped molecule FDT‐8 into a highly favored structure, namely, a vertical stack. Thermal annealing of films of FDT‐8 deposited on PEDOT: PSS coated ITO substrates was observed to assist the organization of the molecules into columnar stacks. A significant enhancement in the hole (≈50‐fold) and the electron (≈13‐fold) carrier mobility was observed in single‐carrier devices upon thermal annealing that could be attributed to the aforementioned self‐organization. The ability of these molecules to spontaneously self‐organize was utilized to fabricate bilayer light‐emitting devices. Abstract : Be direct ! Directed self‐assembly of FDT‐8 on polar substrates leads to a desired molecular stack yielding a hexagonal columnar arrangement. The resulted molecular arrangement led to a drastic enhancement in charge carrier mobility measured using single‐carrier diodes. A balanced charge carrier mobility was observed and a bilayer EL device was demonstrated using FDT‐8 .